Confidence building in emerging markets - Enrico C. Perotti; Luc Laeven (Fondazione Eni Enrico Mattei (FEEM), 2001)
Investor confidence is a necessary condition for the development of emerging markets. Investors recognize that since market-oriented reform policies may be reversed or hindered, they face the risk of ex post policy changes with redistributive impact on investment returns. We argue that a sustained privatization or liberalization program represents a major test of political commitment, and contributes to reduced policy risk. The evidence from our panel study suggests that progress in privatization gradually leads to increased confidence. Moreover, increased confidence has a strong effect on local market development and is a significant determinant of excess returns. We conclude that, just as financial liberalization, the resolution of policy risk resulting from successful privatization has been an important source for the broadening and deepening of emerging stock markets.
Keywords: G15; L33; F13; 330; International financial markets; privatisation; financial liberalization; Aufstrebende Märkte; Aktienmarkt; Kapitalanlage; Vertrauen; Privatisierung; Finanzmarktregulierung; Theorie